Chemotherapy and terminal skeletal muscle differentiation in WT1‐mutant Wilms tumors. (15th March 2018) - Royer‐Pokora, Brigitte; Beier, Manfred; Brandt, Artur; Duhme, Constanze; Busch, Maike; de Torres, Carmen; Royer, Hans‐Dieter; Mora, Jaume
Abstract: Wilms tumors (WT) with WT1 mutations do not respond well to preoperative chemotherapy by volume reduction, suggesting resistance to chemotherapy. The histologic pattern of this tumor subtype indicates an intrinsic mesenchymal differentiation potential. Currently, it is unknown whether cytotoxic treatments can induce a terminal differentiation state as a direct comparison of untreated and chemotherapy‐treated tumor samples has not been reported so far. We conducted gene expression profiling of 11 chemotherapy and seven untreated WT1 ‐mutant Wilms tumors and analyzed up‐ and down‐regulated genes with bioinformatic methods. Cell culture experiments were performed from primary Wilms tumors and genetic alterations in WT1 and CTNNB1 analyzed. Chemotherapy induced MYF6 165‐fold and several MYL and MYH genes more than 20‐fold and repressed many genes from cell cycle process networks. Viable tumor cells could be cultivated when patients received less than 8 weeks of chemotherapy but not in two cases with longer treatments. In one case, viable cells could be extracted from a lung metastasis occurring after 6 months of intensive chemotherapy and radiation. Comparison of primary tumor and metastasis cells from the same patient revealed up‐regulation of RELN and TBX2, TBX4 and TBX5 genes and down‐regulation of several HOXD genes. Our analyses demonstrate that >8 weeks of chemotherapy can induce terminal myogenic differentiation in WT1 ‐mutant tumors, but this is not associated with volume reduction. The time needed for all tumor cells to achieve the terminal differentiation state needs to be evaluated. In contrast, prolonged treatments can result in genetic alterations leading to resistance. Abstract : Chemotherapy can induce terminal skeletal muscle differentiation in WT1‐mutant Wilms tumors. However, chemotherapy can result in the evolution of genetically aberrant cells conferring resistance.